Giussani’s Experiential Approach to Consciousness and Neuroscience - Mauro Ceroni (Recent Progress in Science and Technology Vol. 6, 2023)
The theme of consciousness has been at the center of modern culture since Descartes codified it with his famous statement: "cogito ergo sum" (I think so I am). The revolutionary character of Descartes is the introduction in the foundation of the philosophical discourse of the "first person" instead of the awe for the Cosmos. The connection between subject and body, as well as consciousness and the brain, appears to still be far from being understood. Every attempts to reduce consciousness and subject to the brain ends up in abolishing the subject, i.e. what is evidently most relevant for each one of us. Luigi Giussani adheres with clarity and loyalty to the cultural turning point of modernity and proposes a method to investigate human consciousness based on the analysis of oneself personal experience, verifiable by every human being. His approach is nevertheless completely comprehensible and open to any input from the field of neuroscience and other scientific research. Giussani’s approach is compared to the fundamental premise that underlies various modern neuroscientific conceptions of consciousness. The approach Giussani suggests might serve as a standard and widely accepted framework for future development and improvements in research on the relationship between the brain and human consciousness, which is our culture’s most pressing issue.